Exploring the Cognitive and Affective Dimensions of Abortion among the Women of Tharu Community of Nepal (A Case Study of Badhaiyatal Rural Municipality, Bardiya) - Acharya, Lalmani (Academia Research Journal, 2023)
This research article aimed to investigate the existing knowledge and attitudes of Tharu women residing in the Badhaiyatal Rural Municipality of the Bardiya district regarding abortion. This research utilized both primary and secondary sources of data to gather comprehensive insights. The sample population consisted of 172 respondents from the Tharu community. The study revealed that a majority of women possessed knowledge about abortion and exhibited a positive attitude towards its legalization. Furthermore, most respondents demonstrated a positive outlook towards safe abortion and its legalization in Nepal. The study objectives included determining the socio-demographic characteristics of the respondents, assessing their knowledge about abortion, and identifying their attitudes towards abortion in the Tharu community. The methodology employed in this research followed a descriptive design with a quantitative nature. The study area encompassed wards No. 4 and 6 of the Badhaiyatal Rural Municipality in the Bardiya district. The target population comprised women of reproductive age (15-49 years), totaling 516 individuals. Systematic random sampling was utilized as the sampling technique. Data collection involved conducting home visits and employing interview schedules and attitude scales for primary data, along with utilizing records from the Tharu Samaj and various publications for secondary data. The findings indicated that 41.86 percent of respondents defined abortion as the expulsion of the fetus before natural birth, while 12.79 percent considered miscarriage as a form of abortion. Furthermore, 33.72 percent strongly disagreed, and 4.07 percent agreed that a fetus is a living being with the right to be born. The study concluded that the majority of respondents were aged between 15 and 25 years, adhered to Hinduism, and were unmarried. Most respondents were aware of abortion’s legalization in Nepal; they lacked knowledge about the specific legal provisions.